Distribution and habitat attributes associated with the Himalayan red panda in the westernmost distribution range. Issue 9 (2nd April 2021) - Shrestha, Saroj; Thapa, Arjun; Bista, Damber; Robinson, Natasha; Sherpa, Ang Phuri; Acharya, Krishna Prasad; Jnawali, Shant Raj; Lama, Sonam Tashi; Lama, Sony
Abstract: The Himalayan red panda ( Ailurus fulgens ), a recently confirmed distinct species in the red panda genus, is distributed in Nepal, India, Bhutan, and south Tibet. Nepal represents the westernmost distribution of the Himalayan red panda. This study aims to determine important habitat features influencing the distribution of red panda and recommend possible habitat corridors. This manuscript described current potential habitat of 3, 222 km 2 with the relative abundance of 3.34 signs/km in Nepal. Aspect, canopy cover, bamboo cover, and distance to water were the important habitat attributes. It suggested five potential corridors in western Nepal. Overall, the study has important implications for conservation of the Himalayan red panda in western distribution range. Abstract : Himalayan red pandas were confined between the range of 2, 600 m–3, 600 m, with most records between 3, 250 m–3, 400 m on the north and west‐facing slopes. The potentially suitable habitat of the red panda in Western Nepal is estimated to be about 3, 222 km 2 with a relative abundance of 3.34 signs/km.